2014
DOI: 10.1016/j.ajpath.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model of Endometriosis Mimics Human Phenotype and Reveals Insights into the Inflammatory Contribution of Shed Endometrium

Abstract: Endometriosis is an estrogen-dependent inflammatory disorder characterized by the presence of endometrial tissue outside the uterine cavity. Patients experience chronic pelvic pain and infertility, with the most likely origin of the tissue deposits (lesions) being endometrial fragments shed at menses. Menstruation is an inflammatory process associated with a dramatic increase in inflammatory mediators and tissue-resident immune cells. In the present study, we developed and validated a mouse model of endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
197
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(209 citation statements)
references
References 44 publications
10
197
0
2
Order By: Relevance
“…We have previously reported that Ccl-2 and Ccl-5 (regulated on activation normal T-cell expressed and secreted) mRNA concentrations were elevated in mouse endometriosis lesions, 9 and herein we show that mRNA concentrations of the chemokine Ccl-3 were also significantly elevated in mouse endometriosis lesions (P < 0.01) compared with biopsy specimens of naïve uterus and peritoneum ( Figure 4D). Figure 4 Macrophage infiltration of lesions is estradiol (E2) dependent in a mouse model of endometriosis.…”
Section: Macrophage Infiltration Of Endometriosis Lesions Is E2 Depensupporting
confidence: 71%
See 4 more Smart Citations
“…We have previously reported that Ccl-2 and Ccl-5 (regulated on activation normal T-cell expressed and secreted) mRNA concentrations were elevated in mouse endometriosis lesions, 9 and herein we show that mRNA concentrations of the chemokine Ccl-3 were also significantly elevated in mouse endometriosis lesions (P < 0.01) compared with biopsy specimens of naïve uterus and peritoneum ( Figure 4D). Figure 4 Macrophage infiltration of lesions is estradiol (E2) dependent in a mouse model of endometriosis.…”
Section: Macrophage Infiltration Of Endometriosis Lesions Is E2 Depensupporting
confidence: 71%
“…Specifically, by using in vitro model systems, we found that DRG neurons produced chemokines in response to E2 that promoted macrophage recruitment, whereas macrophages stimulated with E2 produced NTs that promoted neuronal outgrowths. By using a mouse model of endometriosis, 9 we demonstrated that macrophage infiltration of endometriosis lesions was E2 dependent and that the concentrations of mRNAs encoding Csf-1, Nt-3, and TrkB were E2 regulated in mouse lesions.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations